(untitled) (International journal of artificial intelligence, 2026)
This article analyzes modern approaches to the formation and development of pedagogical skills in future teachers. It highlights the essence of pedagogical mastery, its main components, and the key factors influencing the development of professional competence. In addition, the importance of innovative technologies, digital platforms, interactive teaching methods, and pedagogical reflection in the educational process is scientifically examined. The role of practical training, mentoring systems, and a creative learning environment in preparing future teachers for professional activity in higher education institutions is also emphasized.